Concerns and Considerations: Creutzfeldt-Jakob Disease in Pakistan and Reusable Laryngoscopes - Ahmed, Maheen; Ahmed, Misha (Journal of the Pakistan Medical Association, 2024)
The world witnessed a transition to single-use laryngoscopes from reusable laryngoscopes with the rise of Creutzfeldt-Jakob disease (CJD). Hill et al. found CJD in tonsillar tissue. (1) Another study reported laryngoscope blades contaminated with lymphocytes after routine laryngoscopy. (2) It is known that prions resist conventional sterilisation techniques. This raises the concern that if a laryngoscope is used on a patient incubating CJD, we could transmit it to the next patient. In Pakistan the usage of reusable laryngoscope is common. Another concern of note is the emerging cases of CJD in our country. A few cases have been reported. (3) Khan et al. did a retrospective review and found 11 cases labelled CJD. (4) Estimating the disease burden of CJD in our country will only be possible if additional institutions can report suspected or encountered cases. It is conceivable that the disease is either genuinely rare or underreported. With a precise estimate of the disease burden, it is easier to determine whether we need a change in practice. Another factor to consider is the environmental footprint of single-use devices. Reusable laryngoscopes produce lower ecological emissions. (5) Lastly, institutions may have to conduct cost assessments comparing the expenses of single-use equipment with labour and cleaning processes associated with reusable equipment, survey their current anaesthetic equipment, and sterilisation practices. We can then determine whether aligning with global standards is the optimal path forward or if the country's existing approach adequately addresses patient and environmental safety concerns.